# Posts by Bosnian

Total # Posts: 2,623

**Math**

1 .) c. sqrt ( 4 ) + sqrt ( 9 ) = 2 + 3 = 5 2 .) b. sqrt ( 36 ) * sqrt ( 49 ) = 6 * 7 = 43 3 .) sq root of - 66 = sqrt ( - 1 ) * sqrt ( 66 ) = i * 8.124 approx. 8 i Remarq ( i ) = sqrt ( - 1 ) 4 .) sqrt ( 3 ) = 1.732 1. 7 round to the nearest tenth c. 5. ) sqrt ( 112 ) = 10....

**math- pre calc/trig**

d = square root ( a ^ 2 + a ^ 2 ) d = square root ( 2 a ^ 2 ) d = square root ( 2 ) * square root ( a ^ 2 ) d = square root ( 2 ) * a 7 square root ( 2 ) = square root ( 2 ) * a Divide both sides by square root ( 2 ) 7 = a a = 7

**Math**

Yes. All negative numbers can be either odd or even. An even number must be integrally divisible by 2. - 2 is an even number. - 2 / 2 = - 1

**math**

1 in = 0.0254 m 1 ft = 12 in = 12 * 0.0254 = 0.3048 1 ft = 0.3048 m 1 ft ^ 2 = ( 0.3048 ) ^ 2 m ^ 2 1 ft ^ 2 = 0,09290304 m ^ 2 75 ft ^ 2 = 75 * 0.09290304 m ^ 2 75 ft ^ 2 = 6.967728 m ^ 2 75 ft ^ 2 = approx. 7 m ^ 2

**Algebra (Quadratics)**

y = ( - 1 / 10 ) x ^ 2 + 3 x + 6 for x = 30 ft y = ( - 1 / 10 ) * 30 ^ 2 + 3 * 30 + 6 = ( - 1 / 10 ) * 900 + 90 + 6 = - 900 / 10 + 90 + 6 = - 90 + 90 + 6 = 6 ft 6 ft > 5 ft The ball will fly over the head of another child.

**Math (Quadractic function)**

a. N ( T ) = 10 T ^ 2 - 20 T + 600 T ( t ) = 3 t + 2 N ( T ( t ) ) = 10 * ( 3 t + 2 ) ^ 2 - 20 * ( 3 t + 2 ) + 600 = 10 * [ ( 3 t ) ^ 2 + 2 * 3 t * 2 + 2 ^ 2 ] - 20 * 3 t - 20 * 2 + 600 = 10 * ( 9 t ^ 2 + 12 t + 4 ) - 60 t - 40 + 600 = 90 t ^ 2 + 120 t + 40 - 60 t - 40 + 600...

**Pre-Calculus**

In the standard ( or general ) form the linear equation is written as: A x + B y = C In this case: A = 3 B = - 2 C = 4 Standard form

**Maths**

b = the number of boys g = the number of girls b / g = 4 / 7 Multiply both sides by 7 7 b / g = 4 Multiply both sides by g 7 b = 4 g Divide both sides by 4 7 b / 4 = g g = 7 b / 4 g = 12 + b 7 b / 4 = 12 + b Subtract b to both sides 7 b / 4 - b = 12 + b - b 7 b / 4 - b = 12 7 ...

**algebra**

a = number of adults c = number of childrens number of adults + number of childrens = 600 total a + c = 600 a * 15 $ + c * 8 $ = 7740 $ 15 a + 8 c = 7740 Now you must solve system of two equations: a + c = 600 15 a + 8 c = 7740 The solutions are : a = 420 c = 180 420 adults ...

**8th grade homework**

Steps: x = a number 1. Six is subtracted from a number: x - 6 2. The result is devided by four: ( x - 6 ) / 4 3. This result is added to 10 to give 30: ( x - 6 ) / 4 + 10 = 30 So : ( x - 6 ) / 4 + 10 = 30 Subtact 10 to both sides ( x - 6 ) / 4 + 10 - 10 = 30 - 10 ( x - 6 ) / 4...

**Algebra**

v1 = an average velocity travel to island = 18 knopts v2 = an average velocity on the return = 10 knots t1 = time of travel to island t2 = time on the return L = Distance betwen harbor and island t = t1 + t2 = total time of trip = 14 h v1 = L / t1 18 = L / t1 L / t1 = 18 v2 = ...

**math**

Enclosure is divide into two equal parts. Thats why you hawe width 3 times. Two times of end of fence and one time in midle. You hawe length 2 times both times of end of fence. So: 3 W + 2 L = 500 3 W = 500 - 2 L = 2 ( 250 - L ) 3 W = 2 ( 250 - L ) Divide both sides by 3 W...

**Maths**

1 h = 60 min 1 min = 1 / 60 1 min = 11 / 60 h 1 min = 0,18333333 h

**Pre-Calculus**

2 x ^ 3 - 3 x ^ 2 - 2 x + 3 = 0 ( 2 x ^ 3 - 2 x ) - 3 x ^ 2 + 3 = 0 _________________________________ Remark : - 3 x ^ 2 + 3 = - ( 3 x ^ 2 - 3 ) _________________________________ ( 2 x ^ 3 - 2 x ) - ( 3 x ^ 2 - 3 ) = 0 2 x ( x ^ 2 - 1 ) - 3 ( x ^ 2 - 1 ) = 0 ( x ^ 2 - 1 ) ( 2 ...

**Pre-Calculus**

x ^ 4 + a x ^ 3 + b x ^ 2 + c x + d = ( x - x1 ) ( x - x2 ) ( x - x3 ) ( x - x4 ) = ( x - 1 ) [ x - ( - 1 ) ] [ x - 2 ) ] ( x - 1 / 2 ) ( x - 1 ) ( x + 1 ) ( x - 2 ) ( x - 1 / 2 ) = x ^ 4 - 5 x ^ 3 / 2 + 5 x / 2 - 1

**algebra 2**

9 | 9 - 8 x | = 2 x + 3 Divide both sides by 9 | 9 - 8 x | = 2 x / 9 + 3 / 9 | 9 - 8 x | = 2 x / 9 + 1 / 3 + OR - ( 9 - 8 x ) = 2 x / 9 + 1 / 3 1. + ( 9 - 8 x ) = 2 x / 9 + 1 / 3 9 - 8 x = 2 x / 9 + 1 / 3 Subtract 9 to both sides 9 - 8 x - 9 = 2 x / 9 + 1 / 3 - 9 - 8 x = 2 x...

**Algebra**

- 2 | 3 y + 7 | + 9 = 5 Subtract 9 to both sides - 2 | 3 y + 7 | + 9 - 9 = 5 - 9 - 2 | 3 y + 7 | = - 4 Divide both sides by - 2 | 3 y + 7 | = - 4 / - 2 | 3 y + 7 | = 2 + OR - ( 3 y + 7 ) = 2 3 y + 7 = 2 Subtract 7 to both sides 3 y + 7 - 7 = 2 - 7 3 y = - 5 Divide both sides ...

**math**

Factor pair : ( - 2 , - 9 ) So : x ^ 2 - 11 x + 18 = ( x - 2 ) ( x - 9 ) = 0

**Algebra II**

a = the first side b = the second side c = the third side P = the perimeter a = 2 b - 5 c = a + 2 = 2 b - 5 + 2 = 2 b - 3 P = a + b + c = 47 a + b + c = 47 2 b - 5 + b + 2 b - 3 = 47 5 b - 8 = 47 Add 8 to both sides 5 b - 8 + 8 = 47 + 8 5 b = 55 Divide both sides by 5 b = 11 ...

**math**

A Prime Numbers can be divided evenly only by 1 or itself. 1 , 3 , 5 , 7 , 11 , 13 ,17 ... 5 is prime number

**Math**

21 / 25 = 4 * 21 / ( 4 * 25 ) = 84 / 100 = 84 %

**math**

68 + 7 = 75 93 + ( 68 + 7 ) = 93 + 75 = 168

**Math**

Yes

**Math**

a ^ m * a ^ n = a ^ ( m + n ) y ^ ( - 9 ) * y ^ 3 = y ^ ( - 9 + 3 ) = y ^ ( - 6 ) = 1 / y ^ 6

**Math**

72 = 2 Ka Divide both sides by 2

**Math**

Ra = Rachel's tall Ke = Kendall's tall Ri = Rich's tall Br = Brian's tall Ra = 2 Ke Ri = Ra + 3 Br = 74 = Ri - 1 74 = Ri - 1 Add 1 to both sides 74 + 1 = Ri - 1 + 1 75 = Ri Ri = 75 in Ri = Ra + 3 75 = Ra + 3 Subtract 3 to both sides 75 - 3 = Ra + 3 - 3 72 = Ra ...

**math**

24 / 12 = 2 72 / 24 = 3 288 / 72 = 4 x / 288 = 5 x = 5 * 288 = 1440 12 , 24 , 72 , 288 , 1440

**math**

(6x^4-x^3+11x^2-2x-2)/(3x+1) = 2x^3-x^2+4x-2 Go on : c a l c 1 0 1 . c o m When page be open click option : long division When page be open in rectangle : Divide type : 6x^4-x^3+11x^2-2x-2 In rectangle : by type : 3x +1 Then click option : DO IT

**Math**

AND 37 = 40 - 3 5 x 37 = 5 x ( 40 - 3 ) = 5 x 40 - 5 x 3

**Math**

37 = 30 + 7 5 x 37 = 5 x ( 30 + 7 ) = 5 x 30 + 5 x 7 3 u + 7 v + 4 u = 2 v Subtract 2 v to both sides 3 u + 7 v + 4 u - 2 v = 2 v - 2 v 3 u + 4 u + 7 v - 2 v = 0 7 u + 5 v = 0

**Calculus-Math**

Go on: c a l c 1 0 1 . com When page be open click option : derivatives When page be open in rectangle : Take the derivative of type : x^7/(7x^3-45x+25) and click option : DO IT You will see solution step-by step

**math**

Possible dates are 11, 13, 15, 17, 19, 21, 23, 25 The only one whose digit add to 4 is 13. She was born on August 13.

**math**

l = 3 w - 7

**Algebra**

5 * ( 14 - 20 ) / 2 = 5 * ( - 6 ) / 2 = -30 / 2 = - 15

**Math**

a = number of ostriches b = number of llamas Numbers of heads = 47 That mean numbers of animals = 47 Numbers of animals = number of ostriches + number of llamas a + b = 47 Numbers of legs = 122 Ostriches have two legs and llamas have four legs so : 2a + 4 b = 122 Now you must ...

**MAth**

| - 1 | = 1 | 4 | = 4 | 3 / - 2 | = 3 / 2 | - 1 | + | 4 | + | 3 / - 2 | = 1 + 4 + 3 / 2 = 5 + 3 / 2 = 5 + 1.5 = 6.5 Correct

**math!**

y = 5 x Divide both sides by 5 y / 5 = x x = y / 5 y = 4 x - 4 y = 4 * ( y / 5 ) - 4 y = 4 y / 5 - 4 Subtract 4 y / 5 to both sides y - 4 y / 5 = 4 y / 5 - 4 - 4 y / 5 y - 4 y / 5 = - 4 5 y / 5 - 4 y / 5 = - 4 y / 5 = - 4 Multiply both sides by 5 y = - 20 x = y / 5 x = - 20 / ...

**fraction**

Remark : 51 / 68 = 3 * 17 / ( 4 * 17 ) = 3 / 4

**fraction**

N = Numerator D = Denominator Conditions : N / D = 3 / 4 2 N = D + 34 N / D = 3 / 4 Multiply both sides by D N = 3 D / 4 2 N = D + 34 2 * 3 D / 4 = D + 34 6 D / 4 = D + 34 Multiply both sides by 4 6 D = 4 D + 136 Subtract 4 D to both sides 6 D - 4 D = 4 D + 136 - 4 D 2 D = 136...

**math**

4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 + 4 ^ 5 = 12 * 4 ^ 5 = 3 * 4 * 4 ^ 5 = 3 * 4 ^ 6 Answer e _____________________________________ Remark: 4 * 4 ^ 5 = 4 ^ 6 becouse: x ^ a * x ^ b = x ^ ( a + b ) so : 4 * 4 ^ 5 = 4 ^ 1 * 4 ^ 5...

**Algebra**

3 y = - 3 Divide both sides by 3

**Algebra**

x -intercept is a point where y = 0 y -intercept is a point where x = 0 x -intercept : 4 x + 3 y = - 3 4 x + 3 * 0 = - 3 4 x + 0 = - 3 4 x = - 3 Divide both sides by 4 x = - 3 / 4 y -intercept : 4 x + 3 y = - 3 4 * 0 + 3 y = - 3 0 + 3 y = - 3 3 x = - 3 Divide both sides by 3 y...

**Algebra**

L = 2 W P = 2 L + 2 W = 2 ( L + W ) 276 = 2 ( L + W ) 276 = 2 ( 2 W + W ) 276 = 2 * 3 W 276 = 6 W Diwide both sides by 6 46 = W W = 46 ft L = 2 W = 2 * 46 = 92 ft Proof: P = 2 ( W + L ) = 2 * ( 46 + 92 ) = 2 * 138 = 276 ft

**Algebra 2**

a = 9 , r = 1 / 2 , n = 12

**Algebra 2**

Geometric Sequences : xn = a * r ^ ( n - 1 ) In this case : a = 9 , r = 1 / 2 xn = a * ( 1 / 2 ) ^ ( n - 1 ) Sum: S = a ( 1 - r ^ n ) / ( 1 - r ) a = 9 , r = 1 /8 2 , n = 12 so : S = 9 * [ 1 - ( 1 / 2 ) ^ 12 ] / ( 1 - 1 / 2 ) = 9 * ( 1 - 1 / 4096 ) / ( 1 / 2 ) = 2 * 9 * ( 4096...

**Algebra 2**

an = 4 * 3 ^ ( 3 - n ) For n = 1 a1 = 4 * 3 ^ ( 3 - 1 ) = 4 * 3 ^ 2 = 4 * 9 = 36 For n = 2 a2 = 4 * 3 ^ ( 3 - 2 ) = 4 * 3 ^ 1 = 4 * 3 = 12 For n = 3 a3 = 4 * 3 ^ ( 3 - 3 ) = 4 * 3 ^ 0 = 4 * 1 = 4 For n = 4 a4 = 4 * 3 ^ ( 3 - 4 ) = 4 * 3 ^ ( - 1 ) = 4 / 3 ^ 1 = 4 / 3 For n = 5 ...

**Math**

Correct

**Math 221**

9 w - w ^ 3 = w ( 9 - w ^ 2 ) _____________________________________ Remark: a ^ 2 - b ^ 2 = ( a - b ) ( a + b ) So: 9 - w ^ 2 = 3 ^ 2 - w ^ 2 = ( 3 - w ) ( 3 + w ) = ( 3 - w ) ( w + 3 ) ( 3 - w ) = - ( w - 3 ) ( 3 - w ) ( w + 3 ) = - ( w - 3 ) ( w + 3 ) ...

**math**

a x ^ 2 + b x + c = 0 The solution to the quadratic equation is given by 2 numbers x1 and x2. We can change the quadratic equation to the form of: a x ^ 2 + b x + c = a ( x - x1 ) * ( x - x2 ) a = 1 so x ^ 2 - 6 x + 12 = 1 * ( x - x1 ) ( x - x2 ) = ( x - x1 ) ( x - x2 ) For : ...

**Trigonometry**

Reiny, Are you sure that the height of the Washington Monument is 171.7 FEET?

**Trigonometry**

Remark: ctg is cotangent ( cot )

**Trigonometry**

Angle in point A = 32 ° tan 32 ° = H / L L = H / tan 32 ° = H * ctg 32 ° Angle in point B = 38 ° tan 38 ° = H / ( L - 55 ) L - 55 = H / tan 38 ° = H * ctg 38 ° L - 55 = H * ctg 38 ° Add 55 to both sides L - 55 + 55 = H * ctg 38 + 55 L = H * ...

**math**

4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 + 4 ^ 8 = 8 * 4 ^ 8 = 2 * 4 * 4 ^ 8 = 2 * 4 ^ 9 = 2 * 262144 = 524288

**Algebra**

x = a number L = x - 2 W = L + 4 = x - 2 + 4 = x + 2 A = L * W = ( x - 2 ) * ( x + 2 ) = x ^ 2 - 2 ^ 2 = x ^ 2 - 4 Answer C _____________________________________ Remark: ( a - b ) ( a + b ) = a ^ 2 - b ^ 2 _____________________________________

**math**

a = first leg b = a + 1 = second leg c = b + 1 = a + 1 + 1 = a + 2 = hypotenuse c ^ 2 = a ^ 2 + b ^ 2 ( a + 2 ) ^ 2 = a ^ 2 + ( a + 1 ) ^ 2 __________________________________ Remark: ( a + b ) ^ 2 = a ^ 2 + 2 * a * b + b ^ 2 __________________________________ a ^ 2 + 2 * a * 2...

**math**

I will not answer all the questions in your homework.

**math**

( a - b ) ^ 2 = a ^ 2 - 2 * a * b + b ^ 2 (4 x - 3 y ) ^ 2 = (4 x ) ^ 2 - 2 * 4 x * 3 y + ( 3 y ) ^ 2 = 16 x ^ 2 - 24 x y + 9 y ^ 2

**math**

1 yd = 3 * 12 = 36 ft 36 * 2.54 = 91.44 1 yd = 91.44 cm

**math**

n = numbers of persons 100 + 20 * n = 25 + 25 * n 100 + 20 n = 25 + 25 n Subtract 25 to both sides 100 + 20 n - 25 = 25 + 25 n - 25 75 + 20 n = 25 n Subtract 20 n to both sides 75 + 20 n - 20 n = 25 n - 20 n 75 = 5 n Divide both sides by 5 75 / 5 = 5 n / 5 15 = n n = 15 Proof...

**math**

C ° = ( 5 / 9 ) * ( F ° - 32 ) ( 5 / 9 ) * ( 95 - 32 ) = ( 5 / 9 ) * 63 = 315 / 9 = 35 ° C

**math**

P = 2 * ( W + L ) P = 24 W = 4 24 = 2 * ( 4 + L ) 24 = 2 * 4 + 2 * L 24 = 8 + 2 L Subtract 8 to both sides 24 - 8 = 8 + 2 L - 8 16 = 2 L Diwide both sides by 2 16 / 2 = 2 L / 2 8 = L L = 8

**math**

5 / 8 = 5 * 3 / ( 8 * 3 ) = 15 / 24 1 / 3 = 8 * 1 / ( 8 * 3 ) = 8 / 24 2 5 / 8 + 1 / 3 = 2 + 5 / 8 + 1 / 3 = 2 + 15 / 24 + 8 / 24 = 2 + 23 / 24 = 2 * 24 / 24 + 23 / 24 = 48 / 24 + 23 / 24 = 71 / 24

**Math**

| x + 4 | = | 3 x + 10 | x + 4 = 3 x + 10 OR x + 4 = - ( 3 x + 10 ) 1 ) x + 4 = 3 x + 10 Subtract x to both sides x + 4 - x = 3 x + 10 - x 4 = 2 x + 10 Subtact 4 to both sides 4 - 4 = 2 x + 10 - 4 0 = 2 x + 6 Subtract 2 x to both sides 0 - 2 x = 2 x + 6 - 2 x - 2 x = 6 Divide ...

**RE: ALGEBRA**

Obviously x = 0 25 x ^ 2 - 10 x = 0 25 * 0 ^ 2 - 10 * 0 = 0 25 * 0 - 10 * 0 = 0 0 - 0 = 0 0 = 0 and 25 x ^ 2 - 10 x = 0 Divide both sides by 5 x 25 x ^ 2 / 5 x - 10 x / 5 x = 0 / 5 x 5 * 5 * x * x / 5 x - 2 * 5 x / 5 x = 0 5 x - 2 = 0 Add 2 to both sides 5 x - 2 + 2 = 0 + 2 5 ...

**Inequalities & Absolute value**

For x = - 2 | 2 x + 4 | < 5 | 2 * ( - 2 ) + 4 | < 5 | - 4 + 4 | < 5 | 0 | < 5 0 < 5 Correct | 5 - 3 x | < 9 | 5 - 3 * ( - 2 ) | < 9 | 5 + 6 | < 9 | 11 | < 9 11 < 9 Not correct 1 correct solution For x = - 1 | 2 x + 4 | < 5 | 2 * ( - 1 ) + 4 | &...

**Math**

When multiplying any number by 0, you get 0. ( 4 / 3 ) * 0 = 0 0 * ( 1 / 2 ) = 0 4/3 multiply by 0 multiply by 1/2 = 0

**math**

xm = 6 ym = 2 x1 = 3 y1 = 5 xm = ( x1 + x2 ) / 2 6 = ( 3 + x2 ) / 2 Multiply both sides by 2 6 * 2 = 2 * ( 3 + x2 ) / 2 12 = 3 + x2 Subtract 3 to both sides 12 - 3 = 3 + x2 - 3 9 = x2 x2 = 9 ym = ( y1 + y2 ) / 2 2 = ( 5 + y2 ) / 2 Multiply both sides by 2 2 * 2 = 2 * ( 5 + y2...

**Math**

9,999 & 10,000 9 + 9 + 9 + 9 = 36 1 + 0 + 0 + 0 + 0 = 1

**Math**

Probably a rectangle . The sides of a rectangle are in the ratio 2 : 1

**maths**

a n = 60 / n a1 = 60 / 1 = 60 a2 = 60 / 2 = 30 a3 = 60 / 3 = 20 a4 = 60 / 4 = 15 a5 = 60 / 5 = 12 a6 = 60 / 6 = 10 12 and 10

**algebra**

9 x + y = 2 Subtract 9 x to both sides 9 x + y - 9 x = 2 - 9 x y = 2 - 9 x –4 x – y = – 17 –4 x – ( 2 - 9 x ) = – 17 - 4 x - 2 - ( - 9 x ) = - 17 - 4 x - 2 + 9 x = - 17 - 4 x + 9 x - 2 = - 17 5 x - 2 = - 17 Add 2 to both sides 5 x - 2 + 2 = - 17...

**Geometry**

The altitude to the base of an isosceles triangle bisects the vertex angle. The altitude to the base of an isosceles triangle bisects the base. L - is the length of a leg B - is the base A - is the altitude A = square root [ L ^ 2 - ( B / 2 ) ^ 2 ]

**Algebra, can some show me how to set this up**

In equation : f(x) = x − 7 replace x with given numbers. f ( 13 ) = 13 - 7 = 6 f ( - 6 ) = - 6 - 7 = - 13 f ( p ) = p - 7

**Math**

30.2 t + 587 = 1432.6 Subtract 587 to both sides 30.2 t + 587 - 587 = 1432.6 - 587 30.2 t = 845.6 Divide both sides by 30.2 t = 845.6 / 30.2 t = 28 1990 + 28 = 2018

**Maths**

Total expenses : 1 / 2 + 1 / 4 + 1 / 5 = 10 / 20 + 5 / 20 + 4 / 20 = 19 / 20 1 - 19 / 20 = 20 / 20 - 19 / 20 = 1 / 20 A person save 1 / 20 part of salary. S / 20 = 50 M ultiply both sides by 20 S = 20 * 50 = 1000

**Math (check answer plz)**

The probability of guessing the correct answer for one question = 1 / 2 ( 1 / 2 ) ^ 12 = 1 / 2 ^ 12 = 1 / 4096 Answer A

**Maths!**

100 , 105, 110, ... 290 , 295 ,300 That is arithmetic progression. The initial term of this arithmetic progression is a1 = 100 The common difference of successive members is d = 5 The n-th term this arithmetic progression an = 300 Use formula for n-th term of the sequence : an...

**algebra**

y = 5 x Divide both sides by 5 y / 5 = x x = y / 5 d = 55 t Divide both sides by 55 d / 55 = t t = d / 55

**Math**

A = h ^ 2 / sqrt ( 3 ) A = 9 ^ 2 / sqrt ( 3 ) A = 81 / sqrt ( 3 ) A = 27 * 3 / sqrt ( 3 ) A = 27 * sqrt ( 3 ) * sqrt ( 3 ) / sqrt ( 3 ) A = 27 * sqrt ( 3 ) Answer J

**pre calculus**

x1 = - 2 x2 = 5 x3 = - 6 y = ( x - x1 ) ( x - x2 ) (x - x3 ) y = [ x - ( - 2 ) ] ( x - 5 ) [ x - ( - 6 ) ] y = ( x + 2 ) ( x - 5 ) ( x + 6 ) y = x ^ 3 + 3 x ^ 2 - 28 x - 60

**algebra**

and x4 - x3 = 7 - 5 = 2

**algebra**

Reiny c) isn't correct answer In w o l f r a m a l p h a . c o m type: interpolate (1,-3),(3,5),(5,11),(7,18) That is a cubic polynomial.

**algebra**

Answer a) x1 = 1 , y1= - 2 x2 = 3 , y2 = 1 x3 = 5 , y3= 4 x4 = 7 , y4 = 7 x2 - x1 = 3 - 1 = 2 x3 - x2 = 5 - 3 = 2 x4 - x3 = 7 - 3 = 2 y2 - y1 = 1 - ( - 2 ) = 1 + 2 = 3 y3 - y2 = 4 - 1 = 3 y4 - y3 = 7 - 4 = 3 Numerically, y increases by 3 units for every 2 unit increase of x.

**math**

x = first number y = second number x + y = 45 Subtract x to both sides x + y - x = 45 - x y = 45 - x square root ( x * y ) = 18 Take square of both sides x * y = 18 ^ 2 x * y = 324 x * ( 45 - x ) = 324 x * 45 - x * x = 324 45 x - x ^ 2 = 324 Subtract 324 to both sides 45 x - x...

**Intermediate algebra**

2 x ^ 2 + 3 = 0 Subtract 3 to both sides 2 x ^ 2 + 3 - 3 = 0 - 3 2 x ^ 2 = - 3 Divide both sides by 2 x ^ 2 = - 3 / 2 Take square root of both sides x = + OR - square root ( - 3 / 2 ) x = + OR - i * square root ( - 3 / 2 )

**Algebra 1--Please, check my answer!**

Correct

**Maths**

A x = b - c x Add c x to both sides A x + c x = b - c x + c x A x + c x = b x ( A + c ) = b Divide both sides by ( A + c ) x = b / ( A + c )

**Algebra 1--Please, check my answer!**

2 t / 4 t ^ 2 + 2 / t = 2 t / ( 2 * 2 * t * t ) + 2 / t = 1 / 2 t + 2 / t = 1 / 2 t + 2 * 2 / 2 t = 1 / 2 t + 4 / 2 t = ( 1 + 4 ) / 2 t = 5 / 2 t Correct Answer

**Algebra can someone guide me**

a ) f ( 13 ) = 13 - 7 = 6 a ) f ( - 6 ) = - 6 - 7 = - 13 c ) f ( p ) = p - 7

**Algebra can someone guide me**

Correction: f ( - 6 ) = - 6 - 7 = - 13

**Algebra can someone guide me**

f ( x) = x − 7 Just replace x with the given values. f ( 13 ) = 13 - 7 = 6 f ( 6 ) = 6 - 7 = 1 f ( p ) = 9 - 7

**Geometry**

V1 = Volume of one sphere: V1 = ( 1 / 6 ) * pi * d ^ 3 V = 30 * V1 V = 30 * ( 1 / 6 ) * pi * d ^ 3 V = ( 30 / 6 ) * pi * d ^ 3 V = 5 * pi * d ^ 3 3,392.92 = 5 * pi * d ^ 3 3,392.92 = 5 * 3.1416 * d ^ 3 3,392.92 = 15.708 * d ^ 3 Divide both sides by 15.708 3,392.92 / 15.708 = ...

**maths**

Remark: Length and width have path 2 meter wide for both sides. That's why we need to reduce their sizes by 2 m * 2 m Area of rectangle : A = a * b where a = L - 2 * 2 = 40 - 2 * 2 = 40 - 4 = 36 m b = W - 2 * 2 = 25 - 2 * 2 = 25 -4 = 21 m So : A = a * b = 36 * 21 = 756 m ^ 2

**maths**

A = ( 40 - 2 * 2 ) * ( 25 - 2 * 2 ) = ( ( 40 - 4 ) * ( 25 - 4 ) = 36 * 21 = 756 m ^ 2

**math**

The graph of a quadratic function is a parabola. If you want to see graph In google type: functions graphs online When you see list of results click on: rechneronline.de/function-graphs When page be open in blue recatacangle type: x ^ 2 + 1 Then click option Draw

**math**

For rule you must give more numbers in Input and Output Table

**maths**

( a + b ) ( a - b ) = a ^ 2 - b ^ 2 ( square root 7 + square root 5 ) ( square root 7 - square root 5 ) = ( square root 7 ) ^ 2 - ( square root 5 ) ^ 2 = 7 - 5 = 2

**maths**

520 - 5 t ^ 2 = 0 520 = 5 t ^ 2 Divide both sides by 5 104 = t ^ 2 t = sqrt ( 104 ) = 10. 198 sec

**math**

[ ( 2600 - 2000 ) / 2000 ] * 100 % = ( 600 / 2000 ) * 100 % = 0.3 * 100 % = 30 %

**Math**

0.8 / 1.6 = 0.5 0.4 / 0.8 = 0.5 0.2 / 0.4 = 0.5 Geometric progression with common ratio q =0 .5